PERBANDINGAN KARAKTERISTIK DASAR ANTARA GRAMEEN BANK DAN BANK SYARIAH DALAM MENGURANGI KEMISKINAN DAN MENINGKATKAN PERTUMBUHAN EKONOMI - Ardi Hamzah; Muhammad Syam Kusufi (InFestasi, 2007)
The elementary characteristic at Grameen Bank with majoritysocial capital than economic capital and also discipline, unity, courage,and hard work and also supported with fundamental belief, sincerity,openness, and help each other able to lessen the poorness and improvethe economic growth. This differ from the Syariah Bank that have goodbase characteristic, but not supported with the development of socialcapital among client and society. The concept of Syariah Bank whichdo not differ far with the Non Syariah Bank with orientation economiccapital that make the imbalance between the bank development withthe society prosperity.